Comparison of Infant feeding practices among rural and urban mothers: an observational study - Singh Yadav, Yogendra; Yadav, Sonali; Rathi, Sunil; Dhaneria, Mamta; Singh, Poonam (International Journal of Medical Research and Review, 2015)
Background: Infant feeding practices are the major determinants of nutritional status of infants and young children. Present study was undertaken to compare the infant feeding practices of rural and urban mothers and the factors influencing these practices. Methods: An observational study was carried out in department of Paediatrics, C R Gardi hospital (CRGH) associated with R D Gardi Medical College (RDGMC), Ujjain Charitable Trust Hospital (UCTH), a unit of C R Gardi Hospital and urban health centre, associated with R D Gardi Medical College, Ujjain. The present study included a total of 1000 children of which 500 were from rural and 500 from urban background over a period of one year. Information on breast feeding and complementary feeding practices was recorded. Results: In the present study, maximum children in both rural and urban areas were between age group of 12-36 months and majority of children of rural area were males. Significantly higher proportion of rural mothers was labourer, illiterate and belongs to low socioeconomic status groups. Majority of rural mothers discarded colostrums and offered prelacteal feeds to their babies. Significantly higher proportion of urban mothers started early initiation of breast feeding after delivery. Formula milk feeding was commoner in urban babies but bottle feeding was significantly higher in rural babies. Conclusion: Feeding practices are poor in rural area so mothers should receive counselling regarding early initiation, colostrum feeding and appropriate complementary feeding practices. Steps should be taken to improve the educational status of females especially among rural mothers.